Critical role of laser microdissection for genetic, epigenetic and proteomic analyses in pancreatic cancer. (September 2011) - Funel, Niccola; Giovannetti, Elisa; Pollina, Luca E; del Chiaro, Marco; Mosca, Franco; Boggi, Ugo; Campani, Daniela
Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease, and molecular studies to unravel novel biomarkers and therapeutic targets are warranted. However, PDAC is characterized by different precursor lesions, as well as by an intense desmoplastic reaction, with islet of neoplastic cells often representing a minor population. Moreover, normal ductal cells, which are considered to be the normal counterpart of pancreatic adenocarcinoma cells, comprise approximately 5% of the total population of cells making up this organ. For all these reasons, molecular techniques to identify critical mutations, as well as the pattern of altered mRNA/microRNA/protein expression should be performed on selected pancreatic cell subpopulations. Therefore, the use of the newest laser microdissection techniques is critical for the analysis of PDAC biological characteristics. This article highlights the most recent and clinically relevant aspects of genetic, epigenetic and proteomic analyses of PDAC from the perspective of the application of laser microdissection.